Kajian Surat Al-Qalam1 dan Surat Al ‘Alaq Q 4 “Alladzi ‘Allama bi al-qolam”: Dalam Perspektif Pentingnya Alat Tulis - Moch. Yaziidul Khoiiri (Intizam, Jurnal Manajemen Pendidikan Islam, 2020)
Stationery is a very important tool for our existence, both for students and other human professions. Because with the stationery, we can record a knowledge conveyed by the teacher, as well as other moments that we consider important. Talking about writing cannot be separated from reading. Both are interrelated with one another. Especially for a student who is struggling with the world of reading and writing every day, therefore it is important to know what is the actual stationery used to record the knowledge given by the teacher, and how it is positioned, and what if the stationery is viewed from its main source namely surah al-Qalam 1, Al 'Alaq 4, "Alladzi' Allama Bi Al-Qolam". The content of surah al-'Alaq which has the meaning of the command to read and surah al-Qolam which has the meaning of ink / pen, this surah is also interconnected, with the presence of ink or stationery, the tuis tool here which is intended more broadly, such as computers and devices other notes. With the existence of a stationery also memeberikan several impacts including: Emerging new ideas, easy ways to remember, stimulating innovation, making a work